2013
DOI: 10.1080/09540121.2013.793263
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and correlates of anxiety and mood disorders among TB- and HIV-infected Zambians

Abstract: We determined the frequency and correlates of current common mental disorders (CMDs) in a consecutive series of 649 adult patients with human immunodeficiency virus (HIV), tuberculosis (TB) or both receiving treatment at 16 primary health care centres across Zambia. Data on socio-demographic variables, clinical disease features, anxiety and mood disorders were collected. The frequency of any anxiety disorder (AD) was 30.8% and major depressive disorder (MDD) 11.3%. Although differences by disease group did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 34 publications
5
26
0
Order By: Relevance
“…In agreement with previous studies, those with less education and those who had trouble understanding written medical information were more likely to report moderate/ severe depressive symptoms, 10,28 which may be due to a lack of understanding of the diagnoses, treatment, and prognosis. Furthermore, our findings confirm that both internalized and external stigma, as measured by items related to shame, social isolation, and plans to disclose TB diagnosis, are important correlates of depressive symptoms in TB-HIV patients.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with previous studies, those with less education and those who had trouble understanding written medical information were more likely to report moderate/ severe depressive symptoms, 10,28 which may be due to a lack of understanding of the diagnoses, treatment, and prognosis. Furthermore, our findings confirm that both internalized and external stigma, as measured by items related to shame, social isolation, and plans to disclose TB diagnosis, are important correlates of depressive symptoms in TB-HIV patients.…”
Section: Discussionsupporting
confidence: 90%
“…We also did not find significant association between HIV co-infection and presence of psychiatric illness. This is consistent with the findings of 29 Deribew A (2010) and 27 van den Heuvel (2013).…”
Section: Discussionsupporting
confidence: 93%
“…Anxiety disorders were the next common morbiditypresent in about 23.5% (n=25) patients. The prevalence of anxiety disorders in our study conforms with the finding by 27 van den Heuvel, 2013, who observed a prevalence of 30.8% for any anxiety disorder. An Indian study published in 2016 reports a prevalence of 39% for anxiety disorders in patients with tuberculosis 5 (Kumar K, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Mental health problems such as anxiety and depression in patients infected with HIV is well documented34. In a study35 that evaluated 649 adult patients with HIV, TB or both, the frequency of any anxiety disorder was 30.8%, and the rates of generalized anxiety disorder were highest for the HIV group. Previous default from TB treatment was also statistically associated with symptoms of anxiety in our study.…”
Section: Discussionmentioning
confidence: 99%